2014
DOI: 10.1002/ar.22933
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Distribution and Arrangement of Herbst Corpuscles in the Oropharynx of the Ostrich (Struthio camelus) and Emu (Dromaius novaehollandiae)

Abstract: Herbst corpuscles are widely distributed throughout the oropharynx of the ostrich and emu in contrast to the general situation in birds. Knowledge of the comparative distribution of Herbst corpuscles in the oropharynx of these two commercially important ratite species may assist in a better understanding of their feeding habits. Tissue sections representing all parts of the oropharynx of five ostrich and five emu heads collected after slaughter were prepared for light microscopy, the Herbst corpuscles counted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
(80 reference statements)
0
28
0
Order By: Relevance
“…The Herbst and Grandry corpuscles are found in both the beak and oral cavity in the domestic duck; however, mainly they are distributed in the caudal part of the beak (Leitner and Roumy 1974). The emu and ostrich are equipped only with the Herbst corpuscles (Crole and Soley 2014). Researchers have determined that skin mechanoreceptors in the rostral part of the beak and in the oral cavity form the so-called bill tip organ (Gottschaldt and Lausmann 1974; Berkhoudt 1980; Gentle and Breward 1986; Halata and Grim 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The Herbst and Grandry corpuscles are found in both the beak and oral cavity in the domestic duck; however, mainly they are distributed in the caudal part of the beak (Leitner and Roumy 1974). The emu and ostrich are equipped only with the Herbst corpuscles (Crole and Soley 2014). Researchers have determined that skin mechanoreceptors in the rostral part of the beak and in the oral cavity form the so-called bill tip organ (Gottschaldt and Lausmann 1974; Berkhoudt 1980; Gentle and Breward 1986; Halata and Grim 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, it may represent a structure that plays a role in absorbing mechanical energy produced by pecking against hard substrates (Crole & Soley, 2016). Meckel's cartilage would possibly prevent nerve fibres within the N. intramandibularis (Crole & Soley, 2016) from creating action potentials by direct mechanical stimulation as opposed to transporting action potentials initiated by mechanoreceptors in the bill tip (Crole & Soley, 2014). Gussekloo and Bout (2005) demonstrated that the forces experienced by the bill tip of the greater rhea during pecking were not great and were sufficiently spread over the bony surface area of the bill tip.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the bill tip of ratite species has received particular attention, initially in the Apterygidae where a bill tip organ was described in five extant kiwi species (Cunningham et al, 2013;Cunningham, Castro, & Alley, 2007). Subsequently, aspects of the rostral bill tips have been studied in the ostrich (Struthio camelus) and emu (Dromaius novaehollandiae) with regards to the bony bill tip (Crole & Soley, 2017), the branches of the trigeminal nerve supplying this region (Crole & Soley, 2016) and the distribution (Crole & Soley, 2014) and structure (Crole, du Plessis, & Soley, 2015) of Herbst corpuscles.…”
Section: Introductionmentioning
confidence: 99%
“…Because the hypoglossal nerve innervates both the tongue and the syrinx, it is finally noted that the evolution of the basicranial nerve foramina may also have been correlated with an increased importance of the tongue in feeding biology. This is possibly indicated by the separation of the foramina nervi vagi et glossopharyngealis in Neognathae, which exit through a single foramen in Enaliornis (Elzanowski & Galton, ) and in Palaeognathae, in which the tongue is rudimentary and exhibits different sensory properties than that of neognathous birds (Crole & Soley, ). Recently, it was furthermore hypothesized that a syrinx evolved late in avian evolution, in the lineage leading to modern birds (Clarke et al, ), and future studies will have to assess whether a refinement of the vocal system accounts for the derived features of the hypoglossus and glossopharyngeus nerves of neognathous birds.…”
Section: Discussionmentioning
confidence: 99%